2012
DOI: 10.2478/v10289-012-0006-x
|View full text |Cite
|
Sign up to set email alerts
|

The Accompanying Fauna of Solitary Bee Osmia Bicornis (L.) Syn. Osmia Rufa (L.) Nests Settled in Different Biotopes

Abstract: Red mason bee Osmia bicornis (L.) is a solitary bee which has been shown to be a successful pollinator of many field crops and greenhouse crops. In favorable environmental conditions, this solitary bee can significantly raise the efficiency of crops. Controlled honeybee farms are invaded by various accompanying fauna. The aim of the study was to find out if the biotope may increase or limit the presence of foreign fauna in the nests of the solitary bee O. bicornis (L.). Four different biotopes were selected: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…We did not identify the pollen in breeding chambers however, these plants were very common within the flight range of female bees, which is 500 to 600 m (Raw, 1972;Gathmann & Tscharntke, 2002). The analysis of nests in this habitat revealed that a high percentage of the larvae were dead or parasitized (Fliszkiewicz et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…We did not identify the pollen in breeding chambers however, these plants were very common within the flight range of female bees, which is 500 to 600 m (Raw, 1972;Gathmann & Tscharntke, 2002). The analysis of nests in this habitat revealed that a high percentage of the larvae were dead or parasitized (Fliszkiewicz et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…This makes red mason bees good candidates for model species, e.g. in studies of pesticide toxicity, the effect of environmental pollution, ecological stoichiometry, or interspecific interactions (Fliszkiewicz et al 2012a;Szentgyörgyi et al 2017;Kierat et al 2018;Sgolastra et al 2019;Filipiak 2019;Eeraerts et al 2020). Females fly throughout the spring until early summer.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcidoid wasps, including Melittobia spp., are known to locate their hosts by means of olfactory cues, emanating either from larvae, cocoons, larval provisions, or larval feces (Vet and Dicke, 1992;Silva-Torres et al, 2005;Cusumano et al, 2010;Filella et al, 2011), and a change in the respective odor may plausibly change host recognition. Pelargonium extrafloral trichome secretions contain anacardic acid derivatives as their main constituents (Gerhold et al, 1984), but also a range volatiles, especially sesquiterpenes (Eltz, pers. obs.).…”
Section: Discussionmentioning
confidence: 99%
“…and leaf-cutter bees (Megachile spp.) (Rank and Goerzen, 1981;Krunic et al, 2005;Fliszkiewicz et al, 2012). A. manicatum has not been recorded as a host in the literature available to us (its nests are rarely found), but it is likely to be parasitized when accessible.…”
Section: Parasitic Wasps and Olfactometer Testsmentioning
confidence: 92%